Un silence sans ambiance. Hammershøi, les impressionnistes et le tournant atmosphérique contemporain - Hugues Choplin (Ambiances)
This article aims at problematizing, from an aesthetic perspective, the contemporary “atmospheric turn”. From a confrontation between French impressionist painting and the painting of the Danish Vilhelm Hammershøi (1864-1916), we thus distinguish three concepts, which define three different aesthetic paths: — the ambience, appropriate to the Impressionists and the philosophies of the situation or, as we will say, of the surroundings; — the atmosphere, implied by the painting as it is thought by a certain French philosophy of the 20th century (Deleuze, Merleau-Ponty, Levinas); — finally, the silence, specific to Hammershøi’s painting. Could this silence, without ambiance or atmosphere, define an art of the common freed from the atmospheric turn?